Regulating Prosecutorial Independence and Impartiality in The Indonesian Criminal Justice System - Afandi, Fachrizal (Kosmik Hukum, 2025)
This article examines prosecutorial independence in Indonesia by analyzing three key aspects: the status of prosecutors as civil servants, the constitutional position of the Prosecution Service, and the role of prosecutors in the criminal justice system. It applies an interdisciplinary legal research method by reviewing laws, regulations, and relevant theories. Understanding these aspects helps assess whether the current legal framework adequately protects prosecutors from external influence and recognizes them as independent legal actors, similar to magistrates in other jurisdictions. Prosecutorial independence and impartiality ensure fairness in the criminal justice system. In Indonesia, prosecutors work as civil servants, similar to those in many inquisitorial systems. However, the law does not clearly define their role as magistrates with judicial authority. This legal uncertainty makes them vulnerable to political and hierarchical pressure, which can influence their decisions. A strong legal framework must protect prosecutors from external interference and allow them to act independently, as magistrates do in other systems. The findings highlight a critical issue: the law classifies prosecutors as civil servants but does not formally recognize them as independent legal actors. This gap allows political leaders, superiors, and other parties to interfere in prosecutorial decisions. Without strong legal protection, prosecutors struggle to maintain impartiality. This article argues that lawmakers must formally recognize prosecutors as independent legal actors, similar to magistrates. Legal reforms should strengthen prosecutorial independence and prevent undue influence. A clear legal framework will protect prosecutors, enhance public trust, and uphold justice in Indonesia.